Spiritual care - 'A deeper immunity' - A response to Covid-19 pandemic - Nicolette V. Roman; Thuli G. Mthembu; Mujeeb Hoosen (AOSIS, 2020)
Coronavirus disease 2019 (COVID-19) has presented unprecedented health challenges across all strata in society throughout the world. The COVID experience has caused us to reflect on quality of life, health and well-being and, just as important, end of life. During this time, spiritual care forms a vital component of holistic health management, especially in terms of coping, coming to terms with illness, suffering and ultimately death. The relationship with the transcendent or sacred has a strong influence on a people's beliefs, attitudes, emotions and behaviour. Populations, communities, families and individuals have always found solace through their religious or philosophical beliefs during times of personal adversity and widespread anxiety or disaster. Although spiritual care has always been a part of the domain of religious beliefs, a more contemporary perspective is that spiritual care forms part of the human psyche and thus forms part of human care, health and well-being for families, patients and healthcare workers. Spiritual care deals with the provision of compassion and empathy during periods of heightened stress, distress and anxiety within care. This article provides insights into the necessity of providing spiritual care as a means of coping and well-being for families, patients and healthcare workers during the COVID-19 pandemic.